Short-acting injectable agarose gel implant
By using BDDE cross-linked agarose in the buffer solution system, the problem of high strength and viscosity of agarose hydrogel implant is solved, and its rapid degradation in the body and good injection performance is achieved. It is suitable for short-acting transplantation Injection agent.
Patent Information
- Application Number
- CN202310992393.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2025-02-18
AI Technical Summary
The existing agarose hydrogel implants have high strength and viscosity when injected, which are difficult to inject, and degrade slowly in the body, making them not suitable as short-acting implants.
By using 1,4-butanediol diglycidyl ether (BDDE) as a crosslinking agent for agarose, crosslinking is performed in a buffer solution system. The crosslinked agarose hydrogel can be directly used after dialysis and homogenization. injection.
The prepared agarose gel implant has good injection performance, accelerated degradation speed and small side effects. It is suitable for short-acting implants, improving patient comfort and treatment convenience.
Smart Images

Figure CN119455103A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a short-acting injectable agarose gel implant. Background Art
[0002] Skin aging is a natural phenomenon, but multiple external factors such as ultraviolet radiation, smoking, unhealthy diet and stress can also accelerate the skin aging process, causing wrinkles, fine lines, sagging, dullness and spots on the skin. In order to delay skin aging and maintain a healthy and youthful appearance, medical cosmetic methods such as injectable skin implants play an important role. Skin implants are medical materials in the form of gels, films or fibers that can be implanted into specific areas of the skin to repair and improve the function and appearance of skin tissue, including filling depressions, smoothing wrinkles, and increasing skin elasticity. Skin implants have a short recovery period and low risk, and can achieve fast, safe and effective skin repair and beauty effects, so they are widely used in the fields of cosmetic medicine and plastic surgery.
[0003] Skin implants are usually made of biocompatible materials that are compatible with skin tissue and gradually degrade in the body to provide support and stimulation for new tissue. The injectability of skin implants is crucial to their application. Injectability allows implants to be accurately injected into the required skin area to achieve targeted treatment. At the same time, injectability allows the implant to accurately control the dosage to ensure that the dosage meets clinical needs and treatment plans. In addition, injectability can reduce trauma and discomfort during the use of skin implants, and improve patient comfort and treatment convenience. Therefore, how to improve the injectability of implant materials is of great significance to improving treatment effects and patient experience.
[0004] Short-acting skin implants are implants that work in a relatively short period of time and are gradually absorbed. Their use has many advantages. The action time of short-acting skin implants is relatively short, which allows treatment plans to be more flexibly adjusted and personalized. Doctors can flexibly adjust the dosage and injection frequency according to the condition and the needs of the patient. At the same time, due to the limited duration of action of short-acting skin implants, the potential side effects are relatively few, reducing the adverse reactions and risks that patients may encounter during treatment. In addition, the effects of short-acting skin implants will gradually fade, and their implantation effects are reversible, which provides better flexibility for patients who need to adjust or discontinue treatment. Therefore, the development of short-acting skin implants is of great significance in the fields of skin disease treatment, beauty and plastic surgery.
[0005] Agarose is a multifunctional natural polysaccharide with good gel properties, biocompatibility and biodegradability, and is widely used in the fields of medicine and bioengineering. Agarose is temperature sensitive and can self-aggregate to form a gel as the temperature changes. At high temperatures, agarose is in the form of a solution, however, at low temperatures, agarose chains will tightly entangle with each other to form a gel structure. Agarose has a certain plasticity and can be adjusted in shape and structure as needed, and can be used as a safe and reliable implant material. However, agarose hydrogel has high strength and viscosity, especially high-concentration agarose, which makes it difficult to be injected. At the same time, the degradation rate of agarose hydrogel in the body is relatively slow, and it is not suitable for use as a short-acting implant.
[0006] The inventor unexpectedly discovered that 1,4-butanediol diglycidyl ether (BDDE) was used as a cross-linking agent for agarose, and cross-linking was performed directly in a buffer solution system. The cross-linked agarose hydrogel was dialyzed and homogenized and can be directly used for injection, and the preparation process is simple and efficient. The agarose gel implant prepared by this method has good injection performance, and the implant can be accurately injected into the required skin area, and the dosage can be accurately controlled, which greatly improves the patient's comfort and treatment convenience. In addition, the agarose gel implant can be degraded quickly, has the advantages of small side effects, good reversibility, and flexible treatment options, and can be used as a short-acting agarose gel implant for convenient use. Summary of the invention
[0007] In view of the above technical problems, the object of the present invention is to provide an agarose hydrogel implant. The agarose hydrogel implant for injection prepared by the present invention is easier to inject when used and degrades rapidly in the body. Specifically, it includes the following contents:
[0008] The present invention provides a short-acting injectable agarose gel implant, and the preparation method of the agarose gel implant comprises the following steps:
[0009] (1) Dissolve agarose in a buffer solution at 90-120°C to obtain a clear and transparent solution A;
[0010] (2) cooling the solution A in step (1) to 40-55° C. to obtain solution B;
[0011] (3) adding a base and a chemical crosslinking agent to the solution B in step (2), stirring and reacting for 2-5 minutes to obtain a uniform solution C;
[0012] (4) The solution C in step (3) is allowed to react at 45-75° C. for 4-24 hours, and then dialyzed and homogenized to obtain an agarose gel implant.
[0013] Preferably, the temperature in step (1) is 105-110°C.
[0014] Preferably, the temperature in step (1) is 45-50°C.
[0015] Preferably, the temperature in step (4) is 45-55°C.
[0016] Preferably, the pH of the buffer solution in step (1) is 6.5 to 7.5.
[0017] Preferably, the pH of the buffer solution in step (1) is 7.0.
[0018] Preferably, the reaction time in step (3) is 3-5 min.
[0019] Preferably, the buffer solution is a phosphate buffer solution.
[0020] Preferably, the base is selected from any one of sodium carbonate, sodium bicarbonate and sodium hydroxide.
[0021] Preferably, the base is sodium hydroxide.
[0022] Preferably, the mass percentage concentration of the sodium hydroxide is 0.1%-1%.
[0023] Preferably, the mass percentage concentration of the sodium hydroxide is 0.1%-0.25%.
[0024] Preferably, the cross-linking agent is 1,4-butanediol diglycidyl ether.
[0025] Preferably, the cross-linking agent is 1,4-butanediol diglycidyl ether with a mass percentage concentration of 1%-3.0%.
[0026] Preferably, the cross-linking agent is 1,4-butanediol diglycidyl ether with a mass percentage concentration of 1%-1.5%.
[0027] Preferably, the content of agarose is 10-25 mg / mL.
[0028] The beneficial effects of the present invention are as follows: the agarose hydrogel implant of the present invention has the following characteristics compared with the agarose hydrogel formed by the physical action of self-aggregation. ① The agarose hydrogel implant of the present invention is prepared by cross-linking with BDDE, retaining the excellent properties of agarose hydrogel, and at the same time, having reduced mechanical strength and viscosity, and the extrusion force required for injection is more uniform, which enhances its injectability and has better application potential in terms of injection and implantation into the skin; ② The agarose hydrogel of the present invention has faster degradation and is suitable for short-acting agarose implants. Compared with the agarose hydrogel prepared by patent CN115260545A, the agarose hydrogel implant of the present invention does not need to add organic dispersants such as dimethyl sulfoxide or anhydrous ethanol, is safer, and has a simpler preparation process. The prepared agarose hydrogel can be used for injection after purification and homogenization without mixing with the base of the muscle solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Injection force diagram of agarose hydrogel;
[0030] Figure 2 Storage modulus and loss modulus plots of agarose hydrogel;
[0031] Figure 3 Shear viscosity diagram of agarose hydrogel;
[0032] Figure 4 Acid degradation rate graph of agarose hydrogel;
[0033] Figure 5 Acid degradation rate diagram of agarose hydrogel prepared at different temperatures;
[0034] Figure 6 Acid degradation rate of agarose hydrogels prepared with different BDDE dosages;
[0035] Figure 7 Acid degradation rate of agarose hydrogels prepared with different sodium hydroxide contents;
[0036] Figure 8 SEM image of agarose hydrogel. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with the examples and drawings, but the present invention is not limited by the following examples. Example 1 Preparation of chemically cross-linked agarose hydrogel
[0038] 1.10 mg / mL (1%) chemically cross-linked agarose hydrogel
[0039] 0.1 g of agarose was dissolved in 10 mL of PBS buffer solution (pH 7.0) at 105°C, stirred and refluxed for 30 min, then cooled to 45°C, 0.1% NaOH and 1% BDDE were added, and stirred for 3 min. The above homogeneous solution was allowed to react at 45°C for 24 hrs, then dialyzed in PBS buffer solution (pH 7.0), and the obtained gel was homogenized to obtain a chemically cross-linked agarose hydrogel with a content of 10 mg / mL (1%).
[0040] 2.25 mg / mL (2.5%) chemically cross-linked agarose hydrogel
[0041] 0.25 g of agarose was dissolved in 10 mL of PBS buffer solution (pH 7.0) at 110°C, stirred and refluxed for 35 min, then cooled to 50°C, 0.25% NaOH and 1.5% BDDE were added, and stirred for 5 min. The above homogeneous solution was allowed to react at 55°C for 24 hrs, then dialyzed in PBS buffer solution (pH 7.0), and the obtained gel was homogenized to obtain a chemically cross-linked agarose hydrogel with a content of 25 mg / mL (2.5%).
[0042] 3.10 mg / mL (1%) LTA hydrogel (Comparative 1)
[0043] 0.1 g agarose was dissolved in 10 mL PBS buffer solution (pH 7.0) at 100° C., stirred and refluxed for 30 min, and then the solution was allowed to stand at 37° C. for 24 hrs. The resulting gel was homogenized to obtain an LTA hydrogel with a content of 10 mg / mL (1%).
[0044] 4.25 mg / mL (2.5%) LTA hydrogel (Comparative 2)
[0045] 0.25 g agarose was dissolved in 10 mL PBS buffer solution (pH 7.0) at 110° C., stirred and refluxed for 35 min, and then the solution was allowed to stand at 37° C. for 24 hrs. The resulting gel was homogenized to obtain an LTA hydrogel with a content of 25 mg / mL (2.5%).
[0046] Example 2 Preparation of chemically cross-linked agarose hydrogel freeze-dried sponge
[0047] The non-homogeneous chemically cross-linked agarose hydrogel prepared in Example 1 was pre-frozen at low temperature for 14 hrs and vacuum-freeze-dried for 24 hrs to form a chemically cross-linked agarose sponge.
[0048] The non-homogeneous self-aggregated LTA hydrogel prepared in Example 1 was pre-frozen at low temperature for 14 hrs, and vacuum freeze-dried for 24 hrs to form a self-aggregated agarose sponge.
[0049] Example 3 Injectability test of chemically cross-linked agarose hydrogel
[0050] Test samples: chemically cross-linked agarose hydrogel and LTA hydrogel prepared in Example 1.
[0051] Use a needle tester to test the needleability of the sample. Install the injection needle and push the core rod at a constant speed. The sample is located in the syringe and is pushed out through the needle. The needleability of the sample is evaluated by measuring the extrusion force curve. By observing the extrusion force curve, you can understand the change in the extrusion force of the sample during the extrusion process. The flatter the extrusion force curve, the smaller the extrusion force, which means that the sample is easy to be extruded and has good injection performance. The injection test results are as follows: Figure 1 shown.
[0052] The results show that the pushing force curve of LTA hydrogel (comparison 1 and 2) varies greatly, especially the high-concentration LTA hydrogel, indicating that the sample is unevenly dispersed, affecting the handiness during injection. The chemically cross-linked agarose hydrogel prepared in Example 1 has a more uniform and gentle pushing force during injection, indicating that the sample is evenly dispersed; and the pushing force required for hydrogel injection is reduced, making the injection of agarose implants easier and significantly improving the injectability of the implants.
[0053] Example 4 Rheological properties test of chemically cross-linked agarose hydrogel
[0054] According to Example 1, a hydrogel with a uniform thickness of 1 cm×1 cm×2 mm was prepared, and then placed on the sample stage of the rheometer. The shear strain of the rheometer was fixed, and the storage modulus G' (Pa) and loss modulus G" (Pa) of the gel were tested as a function of angular frequency.
[0055] The rheological properties test results of the agarose hydrogel prepared in Example 1 are as follows: Figure 2 As shown. When the angular frequency is 2.07rad / s, the storage modulus of LTA hydrogel (Comparison 1) is 18428Pa, and the storage modulus of 10mg / mL (1%) chemically cross-linked agarose hydrogel is 612.76Pa; the storage modulus of LTA hydrogel (Comparison 2) is 89702Pa, and the storage modulus of 25mg / mL (2.5%) chemically cross-linked agarose hydrogel is 5056.6Pa. Compared with the comparative example LTA hydrogel, the storage modulus and loss modulus of the chemically cross-linked agarose hydrogel of the present invention are significantly reduced, which is conducive to the injection of agarose.
[0056] Example 5 Shear viscosity test of chemically cross-linked agarose hydrogel
[0057] The hydrogel with a uniform thickness of 1 cm×1 cm×2 mm prepared according to Example 1 was then placed on the sample stage of a rheometer. -1 ~1 000s -1 The peristaltic scanning was performed under the condition of , and the shear viscosity of different gels was obtained. The test results are shown in Figure 3 shown.
[0058] The results showed that as the shear rate increased, the viscosity of the hydrogel in Example 1 decreased, indicating that the agarose gel had a shear thinning effect, which was beneficial to the injection of the agarose hydrogel.
[0059] Example 6 In vitro degradation test of chemically cross-linked agarose hydrogel
[0060] Test sample: liposugar hydrogel freeze-dried sponge prepared in Example 2.
[0061] Weigh appropriate amounts (W0) of the four freeze-dried samples prepared in Example 2 and place them in centrifuge tubes to reach swelling equilibrium in PBS buffer, and then soak them in PBS buffer containing 1.5M hydrochloric acid at 37°C to characterize the degradation behavior of the hydrogel. Samples were taken at regular intervals, the supernatant was removed after centrifugation, and the precipitate was freeze-dried and weighed (W t The acid degradation rate was calculated according to the following formula: Weight loss (%) = (W0-W t ) / W0×100%. The results of in vitro degradation behavior are shown in Figure 4 .
[0062] The results showed that compared with the self-aggregating agarose hydrogels described in Comparisons 1 and 2, the in vitro degradation rate of the chemically cross-linked agarose hydrogels described in the present invention was significantly accelerated, and was suitable for short-acting agarose implants.
[0063] Example 7 Effect of reaction temperature on the preparation of agarose hydrogel
[0064] 0.1g agarose was dissolved in 10mL PBS buffer solution (pH7.0) at 105℃, stirred and refluxed for 30min, then cooled to 45℃, 0.25% NaOH and 1.5% BDDE were added, and stirred for 3min. The above uniform solution was reacted at 45℃, 55℃, 65℃, 75℃, 85℃, 95℃ and 105℃ for 24hrs to obtain reaction products. Among the reaction products taken out, only 45℃, 55℃, 65℃ and 75℃ could form gel; while at 85℃, 95℃ and 105℃, it was still a transparent solution and failed to form gel.
[0065] The acid degradation results of agarose gel formed at 45℃, 55℃, 65℃ and 75℃ are as follows Figure 5The results showed that the agarose gel formed at 75°C degraded fastest, while the agarose gel formed at 45°C degraded slowest.
[0066] Example 8 Effect of BDDE Dosage on Preparation of Agarose Hydrogel
[0067] 0.1g agarose was dissolved in 10mL PBS buffer solution (pH7.0) at 105°C, stirred and refluxed for 30min, then cooled to 45°C, 0.25% NaOH was added, and 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5% and 3% BDDE were added respectively, and stirred for 3min. The above uniform solution was reacted at 45°C for 24hrs to obtain a reaction product. Among the reaction products taken out, 1%, 1.5%, 2%, 2.5% and 3% BDDE dosages can form gels, while 0.1% and 0.5% BDDE dosages are still solutions and gel formation fails.
[0068] The acid degradation results of agarose gels formed by 1%, 1.5%, 2% and 2.5% BDDE are shown in Figure 2. Figure 6 The results show that the degradation rate of hydrogel is the slowest when the dosage of BDDE is 1%, and there is no significant difference in the degradation rate when the dosage of BDDE is 1.5% or above.
[0069] Example 9 Effect of NaOH dosage on the preparation of agarose hydrogel
[0070] 0.1 g of agarose was dissolved in 10 mL of PBS buffer solution (pH 7.0) at 105°C, stirred and refluxed for 30 min, then cooled to 45°C, 1.25%, 1%, 0.75%, 0.5%, 0.25% and 0.1% NaOH were added respectively, and then 1.5% BDDE was added and stirred for 3 min. The above uniform solution was reacted at 45°C for 24 hrs to obtain a reaction product. Among the reaction products taken out, only when the NaOH content was 1.25%, gel could not be formed.
[0071] The acid degradation results of agarose gel formed by 1%, 0.75%, 0.5%, 0.25% and 0.1% NaOH are shown in Figure 7 The results show that the degradation rate of hydrogel is the fastest when the dosage of NaOH is 1%, and the degradation rate of hydrogel is the slowest when the dosage of NaOH is 0.1%.
[0072] Example 10 Scanning electron microscopy (SEM) characterization of chemically cross-linked agarose hydrogel
[0073] The 1% agarose hydrogel freeze-dried sponge sample prepared in Example 2 was fixed on the sample stage of a scanning electron microscope, sprayed with gold for 25 seconds, and the sample morphology was detected by scanning electron microscope at an operating voltage of 5.0 kV. The results of scanning electron microscopy (SEM) are shown in FIG. Figure 8 As shown, the mesh of the self-aggregated agarose sponge is dense, and the mesh of the chemically cross-linked agarose sponge of the present invention is larger, and there is a large difference in the microscopic morphology.
[0074] In summary, the present invention uses 1,4-butanediol diglycidyl ether (BDDE) as a cross-linking agent of agarose, and is directly cross-linked in a buffer solution system. The cross-linked agarose hydrogel can be directly used for injection through dialysis homogenization, and the preparation process is simple and efficient. The agarose gel implant prepared by the method has good injection performance, greatly improving the comfort and treatment convenience of the patient. In addition, the agarose gel implant can be degraded faster, has the advantages of small side effects, flexible treatment schemes, and can be used as a short-acting agarose gel implant for convenient use.
[0075] The above description is only the details of individual exemplary implementation cases of the present invention. For those skilled in the art, the present invention may have various modifications and changes according to specific preparation conditions during actual application, and is not intended to limit the present invention. Anything within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A short-acting injectable agarose gel implant, characterized in that: The preparation method of the agarose gel implant comprises the following steps: (1) Dissolve agarose in a buffer solution at 90-120°C to obtain a clear and transparent solution A; (2) cooling the solution A in step (1) to 40-55° C. to obtain solution B; (3) adding a base and a chemical crosslinking agent to the solution B in step (2), stirring and reacting for 2-5 minutes to obtain a uniform solution C; (4) The solution C in step (3) is allowed to react at 45-75° C. for 4-24 hours, and then dialyzed and homogenized to obtain an agarose gel implant.
2. The agarose gel implant according to claim 1, characterized in that The pH of the buffer solution in step (1) is 6.5 to 7.
5.
3. The agarose gel implant according to claim 2, characterized in that: The pH of the buffer solution in step (1) is 7.
0.
4. The agarose gel implant according to claim 1, characterized in that: The buffer solution is a phosphate buffer solution.
5. The agarose gel implant according to claim 1, characterized in that: The alkali is selected from any one of sodium carbonate, sodium bicarbonate and sodium hydroxide.
6. The agarose gel implant according to claim 5, characterized in that: The base is sodium hydroxide.
7. The agarose gel implant according to claim 6, characterized in that: The mass percentage concentration of the sodium hydroxide is 0.1%-1%.
8. The agarose gel implant according to claim 1, characterized in that: The cross-linking agent is 1,4-butanediol diglycidyl ether.
9. The agarose gel implant according to claim 8, characterized in that: The cross-linking agent is 1,4-butanediol diglycidyl ether with a mass percentage concentration of 1%-3.0%.
10. The agarose gel implant according to claim 1, characterized in that: The content of the agarose is 10-25 mg / mL.
Citation Information
Cited By
Composite implant containing agarose with different molecular weights as well as preparation method and application of composite implant
CN120154754A
A composite implant containing agarose of different molecular weights, its preparation method and application
CN120154754B